On the Issue of Types, Variants and Derivations of a Compound Complex Sentence - Štěpán, Josef (Bohemica Olomucensia, 2024)
The paper describes seven types of compound complex sentences (i. e. sentence consisting of more than two clauses) based on the individual connectives, clause-order variants of these types, modality variants and derivation of the types and clause-order variants.
Keywords: Clause-Order; Compound Complex Sentence; Subordinate Clause; Hypotactic Connectives; Main Clause; Paratactic Connectives; Syntax